Pengaruh digital public relations terhadap kepercayaan dan loyalitas nasabah bank syariah : strategi influencer marketing dalam komunikasi syariah - Ariwibowo, Yusuf Ageng (Maliki Interdisciplinary Journal, 2025)
The development of information technology has transformed communication patterns between financial institutions and society. In the context of Islamic banking, Digital Public Relations (Digital PR) has become an essential strategy for building a positive image, increasing trust, and maintaining customer loyalty. This study aims to describe and analyze the influence of Digital Public Relations on customer trust and loyalty in Islamic banks in Indonesia. The research method used is library research, which involves reviewing relevant literature, academic journals, and previous studies related to the topic. The findings indicate that the implementation of Digital Public Relations through social media, websites, and digital campaigns can strengthen the relationship between Islamic banks and their customers. Transparent two-way communication, educational content on Islamic finance, and prompt responses to public inquiries play significant roles in establishing trust. Moreover, the trust built through effective digital communication contributes directly to increased customer loyalty. Thus, Digital Public Relations serves as a strategic instrument to enhance the reputation and sustainability of Islamic banks in the era of digital transformation.